G284(P) The future of paediatrics in 20 years time. (27th April 2016) - Stoll, S; Congdon, L; Fertleman, C
Abstract : Background: Huge advances have taken place in Paediatrics in recent history. From a mortality rate of 121.3 per 1, 000 live births in 1922 to 4.6 per 1000 in 2013. 1 This reduction has been the result of many advances such as the introduction of surfactant and insulin. This leads onto the questions of what will Paediatrics look like in 20 years? Which problems will Paediatricians face and what diseases will be cured? Will the majority of Paediatricians be based in hospital and will technology change the current face-to-face patient contact? Aims: These questions will be addressed to gain a picture of the future of Paediatrics in 20 years' time. Method: A qualitative survey was conducted from 20 Paediatricians in a district general hospital. Results: This survey found that in our current climate of political uncertainty, only 35% of doctors think the NHS will still exist in 20 years' time. The majority of doctors believe our greatest challenge will be in staffing and financing. They feel there could also be a 'new subset of surviving children with previous younger morality', which would increase demand for services. Most doctors' feel that consultations will remain face-to-face and will not become virtual. They felt our greatest advances will be in managing viruses and gene therapy (20% responses mentioned Cystic Fibrosis). A majority of Paediatricians see a change in dealing with mental health in children and one stated that 'with breaking down of taboo of mental health, better provision will happen'. Conclusion: The specific advances that we are most likely to see in the future have been identified in this survey with notable focus on gene therapy. Additionally, most Paediatricians believe patient contact will still be face-to-face, but the importance of technology and the greater access of information to patients are vital to consider in the future of Paediatrics. Reference: Max Roser (2015) – 'Child Mortality'. Published online at OurWorldInData.org. Retrieved from: http://ourworldindata.org/data/population-growth-vital-statistics/child-mortality/ [Online Resource]